Energy models for 2000 and beyond - "Parikh, Jyoti" (Delhi, 1997)
This book contains six energy models developed over a period of more than ten years. Two of the models have been developed with my colleagues and the others in association with my Ph D students, and these have also been used for their thesis work.
Keywords: Energy